1995
DOI: 10.1111/j.1744-7917.1995.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

FLIGHT ACTIVITY AND FATTY ACID UTILIZATION IN MYTHIMNA SEPARATA (WALKER) MOTHS*

Abstract: The fatty acid (FA) compositions for total lipids from fat body, hemolymph and flight muscle of the armyworm moths, Mythirnna separata, at rest and after tethered flight for 1 h were determined by GC and GC‐MS. The composition in these tissues comprises myristic acid (1%‐2%), palmitic acid (more than 35%1, palmitoleic acid (9%‐11%), stearic acid (less than 1%), oleic acid (about 32%), linoleic acid (12%‐17%) and linolenic acid (3%‐6%). After flight, FA level in the fat body, compared to that at rest, shows a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The decline in the NFAs OL and PA, as well as the δ 13 C value of the fat body, as a function of flight duration in 5-day old moths supports the idea that adult-derived FAs are preferentially used by the true armyworm to fuel flight, as reported for other insects (Schneider and Dorn, 1994;Wang and Ouyang, 1995;Murata and Tojo, 2002;Sakamoto et al, 2004;Levin et al, 2017). Furthermore, the fact that following flight the levels of LA and ALA in the fat body decline in moths reared under summer conditions but not in those reared under fall conditions (Tables 2, 3) support our hypothesis of differential FA allocation under different environmental conditions.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The decline in the NFAs OL and PA, as well as the δ 13 C value of the fat body, as a function of flight duration in 5-day old moths supports the idea that adult-derived FAs are preferentially used by the true armyworm to fuel flight, as reported for other insects (Schneider and Dorn, 1994;Wang and Ouyang, 1995;Murata and Tojo, 2002;Sakamoto et al, 2004;Levin et al, 2017). Furthermore, the fact that following flight the levels of LA and ALA in the fat body decline in moths reared under summer conditions but not in those reared under fall conditions (Tables 2, 3) support our hypothesis of differential FA allocation under different environmental conditions.…”
Section: Discussionsupporting
confidence: 74%
“…Min et al (2004) reported a post flight increase in JH titers for migratory grasshoppers, and Cusson et al (1990) reported increased JH production when TAW adults experienced an increase in ambient temperature. Thus, if increasing body temperature following flight resulted in higher JH levels and led to higher consumption of resources, it would result in greater changes in levels of OL compared with the other FAs, as it is one of the most readily used fuel sources in insects (Schneider and Dorn, 1994;Wang and Ouyang, 1995;Tomcala et al, 2010).…”
mentioning
confidence: 99%